Reducing neonatal mortality associated with preterm birth: gaps in knowledge of the impact of antenatal corticosteroids on preterm birth outcomes in low-middle income countries - McClure, Elizabeth M. (2016)
The Global Network’s Antenatal Corticosteroids Trial (ACT), was a multi-country, cluster-randomized trial to improve appropriate use of antenatal corticosteroids (ACS) in low-resource settings in low-middle income countries (LMIC). ACT substantially increased ACS use in the intervention clusters, but the intervention failed to show benefit in the targeted < 5th percentile birth weight infants and was associated with increased neonatal mortality and stillbirth in the overall population. In this issue are six papers which are secondary analyses related to ACT that explore potential reasons for the increase in adverse outcomes overall, as well as site differences in outcomes. The African sites appeared to have increased neonatal mortality in the intervention clusters while the Guatemalan site had a significant reduction in neonatal mortality, perhaps related to a combination of ACS and improving obstetric care in the intervention clusters. Maternal and neonatal infections were increased in the intervention clusters across all sites and increased infections are a possible partial explanation for the increase in neonatal mortality and stillbirth in the intervention clusters, especially in the African sites. The analyses presented here provide guidance for future ACS trials in LMIC. These include having accurate gestational age dating of study subjects and having care givers who can diagnose conditions leading to preterm birth and predict which women likely will deliver in the next 7 days. All study subjects should be followed through delivery and the neonatal period, regardless of when they deliver. Clearly defined measures of maternal and neonatal infection should be utilized. Trials in low income country facilities including clinics and those without newborn intensive care seem to be of the highest priority.